1D thermo-fluid dynamic modelling of de-NOx SCR systems for diesel engine exhaust gas after-treatment. (5th May 2006) - Montenegro, G.; Onorati, A.
A 1D thermo-fluid dynamic computational model has been developed to simulate the unsteady reacting flows inside the SCR (Selective Catalytic Reduction) after-treatment systems of diesel engines. The standard SCR reaction, extended with a detailed NH3 adsorption and desorption mechanisms, and two reactions of urea decomposition, namely the thermolysis and hydrolysis, have been taken into account. Calculations under steady-state conditions have been carried out to validate the urea decomposition model, showing a good correlation with the experimental results available in the literature. The adsorption/desorption model has been validated as well, using different catalysts available on the market and comparing the results with experimental measurements. Furthermore, a diesel engine configuration has been considered to test the SCR model under different operating conditions, to point out the effects of flow unsteadiness over the de-NOx efficiency and also the risk of ammonia slip at the outlet of the SCR device.